Building microclimate and summer thermal comfort in free-running buildings with diverse spaces: A Chinese vernacular house case - Du, Xiaoyu; Bokel, Regina; van den Dobbelsteen, Andy (A+BE | Architecture and the Built Environment, 2019)
In this paper, the authors first clarify the definition of building microclimate in free-running buildings and the relationship with summer thermal comfort. Next, field measurements were conducted to investigate the microclimate in a Chinese traditional vernacular house. Subsequently, the results of measurements were compared with a dynamic thermal and a CFD simulation in order to determine the building microclimate and thermal comfort of the present vernacular house over the period of an entire summer. The field measurements show the present Chinese vernacular house has its own independent building microclimate in summer, which is in accordance with the main character of microclimate in terms of different distributions of solar gain, air temperature and wind velocity in different spaces. The simulation results of the vernacular house could be matched well with the field measurements. According to the simulations, at night, a comfortable temperature could be obtained throughout most of the summer period whereas in the daytime the operative temperature was higher than the comfortable temperature for one-third of the summer period. Wind velocity in the semi-outdoor and outdoor spaces however, improves the thermal comfort significantly. The thermal comfort environment can thus not only change in time but also in space. This example of the vernacular building shows that it is possible to create comfortable conditions for the inhabitants when not only the indoor climate is taken into account but the whole building microclimate as defined in this paper. This paper also shows that the simulations can predict the building microclimate.